2022
DOI: 10.1007/s12204-022-2454-1
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Effects of Ambient Air Pollutants on Outpatient Visits for Childhood Allergic Diseases in Shanghai, China

Abstract: The island paradigm for the fine-grained entropy of Hawking radiation is applied to eternal charged accelerating black holes. In the absence of the island, the entanglement entropy grows linearly and divergent at late times, while once the island outside the event horizon is taken into account, the unitary Page curve is reproduced naturally.The impact of the charge and the acceleration is investigated at late times. For the Page time and the scrambling time, they both increase as the acceleration increases, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…As the institute expanded, the team size grew, with notable collectors including Y.Tsiang, C.L.Tso, N.K.Chun, C.Wang, S.P.Ko, F.C.How, and others ( Table 6 ). This period marked the transition to large-scale collection efforts, with numerous specimens being gathered in Guangzhou between 1928 and 1936 by these collectors and their teams [ 17 ].…”
Section: Brief History Of Plant Collection In Guangzhou City and Its ...mentioning
confidence: 99%
“…As the institute expanded, the team size grew, with notable collectors including Y.Tsiang, C.L.Tso, N.K.Chun, C.Wang, S.P.Ko, F.C.How, and others ( Table 6 ). This period marked the transition to large-scale collection efforts, with numerous specimens being gathered in Guangzhou between 1928 and 1936 by these collectors and their teams [ 17 ].…”
Section: Brief History Of Plant Collection In Guangzhou City and Its ...mentioning
confidence: 99%
“…[28] The polymer's quality mainly depends on the degree of polymerization, which can be calculated by the intrinsic viscosity. [29] Therefore, predicting the intrinsic…”
Section: The Background and Motivationmentioning
confidence: 99%
“…In addition, we use the running time to measure the predictive efficiency.We use the CS algorithm to optimize the parameters a, b, and α in the hybrid Copula function. The fitness function and constraints are shown in Equation(29).…”
mentioning
confidence: 99%
“…While there are no unanimous conclusions about the difference in yield and quality of vegetables under various cultivation modes. Several studies have found that compared to soil cultivation, substrate cultivation could increase the yield and overall quality of green vegetables and spinach [4], and hydroponic cultivation elevated the vitamin C content and reduced nitrate content of lettuce [5]. However, Roman cauliflower cultivated in substrate cultivation had lower fresh weight and soluble solids content than those cultivated in soil [6].…”
Section: Introductionmentioning
confidence: 99%